IMPLEMENTASI KEBIJAKAN KABUPATEN LAYAK ANAK DALAM UPAYA PEMENUHAN HAK-HAK ANAK DI KABUPATEN BREBES - Iqbal Azizi; Herbasuk Nurcahyanto (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
Fulfillment of children's rights needs to be improved by the Government for the success of future development. There are still children's rights whose civil rights have not been fulfilled, child marriage, limited child-friendly infrastructure, high maternal and infant mortality rates, malnutrition and stunting, low school participation rates and cases of child violence. The purpose of this study was to describe and analyze the implementation of Child Friendly District policies in an effort to fulfill children's rights in Brebes Regency along with the driving and inhibiting factors. This research uses a qualitative descriptive research type. The informant determination technique used was purposive sampling with data collection methods through interviews, observation and documentation. The results showed that the implementation of Child Friendly District policies in an effort to fulfill children's rights in Brebes Regency was good, seen by the Government's commitment through Regional Regulation No. 4 of 2014, the establishment of Child Friendly District Task Forces and various programs or activities to fulfill children's rights. Although, the fulfillment of children's rights has not been fully optimal due to sectoral interests, communication between organizations is not going well and the economic, social and political environment is not yet conducive